IBM System z Personal Development Tool messages and codes - Ogden, Bill (Computer programmer) (IBM redbooks., 2016)
This IBM® Redbooks® publication provides all the messages that are associated with IBM System z® Personal Development Tool (IBM zPDT®) operation in a single reference source. This edition is intended for zPDT Version 1 Release 6 (commonly known as GA6), but should be useful for all zPDT releases.